Predicting vertebrate promoters using heterogeneous clusters. (1st October 2010) - Leu, Fang-Yie; Yang, Lun-Ni; Lo, Neng-Wen; Lin, I-Long
This paper proposes a system, named the Vertebrate Promoter Prediction System (VePPS), which employs a new statistics-based approach to predict vertebrate promoters, and analyses a putative promoter sequence by investigating the presence of short promoter-specific sequences and known transcription factor binding sites. In comparison with other prediction programmes, our VePPS outperformed, e.g., promoter 2.0, by 38.0% and 12.7% in predicting promoter and non-promoter sequences, respectively.